2012
DOI: 10.5402/2012/898650
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion and Wear Properties of Composite Coatings Reinforced with Particles Produced by PTA on Steel Substrate in Different Atmospheres

Abstract: Titanium diboride (TiB 2 ) and titanium carbonitride (Ti(C,N)) coatings are widely used as reinforcing materials in applications demanding high corrosion and wear resistance. In this paper, plain carbon steel has been surface alloyed with TiB 2 by plasma transferred arc (PTA) technique using two different gas atmospheres. The first metal matrix composite (MMC) is produced with TiB 2 particles and argon as shielding and plasma gas. In addition, a mixture of Ar and 5% N 2 was used as shielding and plasma gas for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
4
2
0
Order By: Relevance
“…5 indicate similar behaviour, with higher current density in the reverse cathodic scan direction, whereas the cathodic curve intersects the forward anodic scan, regardless of the specimen condition. This fact confirms that the substrate materials as well as both laser-alloyed coating in the as processed condition are susceptible to pitting corrosion [13]. A similar result was also found in the work of Darabara et al [13] who found that TiB2 and TiB2 + N alloyed layers are susceptible to pitting corrosion in 3.5 wt.% NaCl and 1 N H2SO4 solution.…”
Section: Cyclic Polarization Scanssupporting
confidence: 79%
See 2 more Smart Citations
“…5 indicate similar behaviour, with higher current density in the reverse cathodic scan direction, whereas the cathodic curve intersects the forward anodic scan, regardless of the specimen condition. This fact confirms that the substrate materials as well as both laser-alloyed coating in the as processed condition are susceptible to pitting corrosion [13]. A similar result was also found in the work of Darabara et al [13] who found that TiB2 and TiB2 + N alloyed layers are susceptible to pitting corrosion in 3.5 wt.% NaCl and 1 N H2SO4 solution.…”
Section: Cyclic Polarization Scanssupporting
confidence: 79%
“…When titanium diboride is immersed in NaCl solution at room temperature, it behaves like a passive metal due to the formation of a surface oxide film (hydrated titanium dioxide), whose protectivity decreases with the temperature and completely vanishes at 65 °C [15], [38]. In salt rich ocean water, a white film of tetravalent oxide titanium TiO2-H2O is formed, which hinders the material dissolution [13], [38]. Titanium carbide is relatively stable in mineral acids and alkali solutions, but decomposes in the presence of oxidizing acids [39].…”
Section: Microstructural Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This fact confirms that both, the untreated Al alloy substrate and laser-alloyed coatings are susceptible to pitting corrosion [60]. Further, although TiC and TiB 2 coating generally exhibit good passivation behaviour in a NaCl solution, the active/Al part of the coatings prevented expressive passive plateau, as the potential continuously increases with increasing current density [1,3,60,61]. Table 1 lists the results of active dissolution potentials obtained from cyclic polarisation tests, including the average values of protective efficiency (P EF ).…”
Section: Cyclic Polarizationsupporting
confidence: 75%
“…Afterwards, increase in anodic current due to a stable pit growth or pit propagation is observed with a well-defined hysteresis in the reverse cathodic region. This fact confirms that both, the untreated Al alloy substrate and laser-alloyed coatings are susceptible to pitting corrosion [60]. Further, although TiC and TiB2 coating generally exhibit good passivation behaviour in a NaCl solution, the active/Al part of the coatings prevented expressive passive plateau, as the potential continuously increases with increasing current density [1,3,60,61].…”
Section: Cyclic Polarizationsupporting
confidence: 62%